The Effect of Nano-Polyphenols Cocoa Whey Protein as Functional Fortification Materials in Terms of Antioxidant Activity and Physicochemical Properties (Faculty of Animal Science Universitas Brawijaya, 2023)
The study aims to understand the interaction between cocoa polyphenol nanoparticles with whey protein isolate (WPI) bond between polyphenol cocoa nanoparticles with whey protein isolate (WPI) and the role of the nanoparticles of cocoa polyphenols as bioactive compounds in the nano-polyphenol cocoa whey protein. The research method is performed using laboratory experiments with a completely randomized design (CRD), followed by Duncan analysis (DMRT) when there are significant or highly significant differences in each treatment. This research focused on the nanoparticles of cocoa polyphenols in the formulation of the nano-polyphenol cocoa whey protein with 4 treatments (T0: 0%, T1: 5%, T2: 10%, T3: 15%) and 3 replications. The observed variables include total phenolic, antioxidant activity, particle size, emulsion activity, and emulsion stability. The difference in the concentration of the nanoparticles of cocoa results in highly significant differences (P<0.01) in total phenolic, antioxidant activity, and particle size. Gave a significant difference (P<0.05) in the emulsion activity, but does not show a significant difference in the emulsion stability (P>0.05). It can be concluded that cocoa 15% nanoparticles (T3) are the best treatment from other treatments and is able to synergize with whey protein isolate (WPI), improve emulsion quality and have natural antioxidant content used as an alternative for food fortification ingredients